Store Atmosphere, Product Range, and Sale Promotions: Influencing Consumer Purchase Decisions at Hero Supermarket: Pengaruh Atmosfer Toko, Ragam Produk, dan Promosi Penjualan terhadap Keputusan Pembelian Konsumen: Studi Kasus di Hero Supermarket - Sabnatia Fanani; Lilik Indayani (Academia Open, 2022)
This research aimed to investigate the influence of store atmosphere, product range, and sale promotions on consumer purchase decisions at Hero Supermarket in Sidoarjo. A quantitative approach was employed, utilizing a non-probability purposive sampling method to collect data from all consumers of Hero Supermarket. The study employed multiple linear regression analysis using SPSS version 25 for Windows. The results revealed that store atmosphere, product range, and sale promotions significantly affect consumer purchase decisions at Hero Supermarket. These findings provide valuable insights into the factors influencing consumer behavior in the retail industry, thereby assisting marketers and managers in developing effective strategies to enhance customer satisfaction and drive sales. Highlights: Store atmosphere significantly influences consumer purchase decisions. A wide range of products enhances consumer buying behavior. Sale promotions play a crucial role in shaping consumer purchasing choices. Keywords: Store Atmosphere, Product Range, Sale Promotions, Consumer Purchase Decisions, Hero Supermarket